ASPEK HUKUM PERLINDUNGAN KONSUMEN PADA LAYANAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI - Kadek Ary Purnama Dewi (Fakultas Hukum Universitas Ngurah Rai, 2019)
Information technology based lending and borrowing services provide more space for consumers to get financial access. But on the other hand, consumers have the possibility of experiencing losses due to inaccuracy in reading the agreement clause. The existence of information technology based lending and borrowing services is regulated in Financial Services Authority Regulation Number 77 / Pojk.01/2016 About Information Technology Based Lending and Borrowing Services. This study discusses two issues of agreement on information technology-based lending and borrowing services and protecting data confidentiality on information technology-based lending and borrowing services. Consumers have the right to get legal protection in enjoying information technology based lending and borrowing services. The legal protection is carried out in the form of an agreement between the organizer and the user. The agreement can be in the form of a standard agreement. The organizer also has an obligation to provide protection for the confidentiality of personal data of consumers.